Development of a Knowledge-Based Energy Damage for evaluating Industrialised Building Systems (IBS) Occupational Health and Safety (OHS) Risk - Abas, Nor Haslinda (2015)
Malaysia’s construction industry has been long considered hazardous, owing to its poor health and safety record. It is proposed that one of the ways to improve safety and health in the construction industry is through the implementation of ‘off-site’ systems, commonly termed ‘industrialised building systems (IBS)’ in Malaysia, which require fewer workers onsite. This is deemed safer, based on the risk concept of reduced exposure; however, no method yet exists for determining the relative safety of various construction methods, including IBS. This thesis presents a comparative evaluation of the occupational health and safety (OHS) risk presented by different construction approaches, namely IBS and traditional methods. The evaluation involved developing a model based on the concept of ‘argumentation theory’, which helps construction designers integrate the management of OHS risk into the design process. In addition, an ‘energy damage model’ was used as an underpinning framework. Development of the model was achieved through three phases. Phase I involved collection of data on the activities involved in the construction process and their associated OHS risks, derived from five different case studies, field observation and interviews. Knowledge on design aspects that have the potential to impact on OHS was obtained from document analysis. Using the knowledge obtained in Phase I, a model was developed in the form of argument trees (Phase II), which represent a reasoning template with regard to options available to designers when they make judgements about aspects of their designs. Inferences from these aspects eventually determined the magnitude of the damaging energies for every activity involved. Finally, the model was validated by panels of experts (Phase III), and revisions and amendments were made to the model accordingly. The model provides a means of evaluating OHS risk among construction workers, which could help designers understand the extent to which their design decisions may impact on OHS and thereby assist them to reduce the risk to an acceptable level. The development of the risk assessment model represents structured knowledge that designers can draw on when making judgments about OHS risks, in the form of argument trees. The model was categorized into several damaging energies, which provides a way to evaluate the risk from start to finish. The research revealed that different approaches/methods of construction projects carried a different level of energy damage, depending on how the activities were carried out. A study of the way in which the risks change from one construction process to another shows that there is a difference in the profile of OHS risk between IBS construction and traditional methods. For example, the potential gravitational damaging energy for certain activities in the in-situ concrete and masonry method can be removed or reduced by the use of IBS/offsite methods such as the wall panel system and the panellised system. This is compatible ii with other researchers’ claims that IBS/off-site is safer and carries significantly less risk in traditional construction. This thesis contributes to knowledge by suggesting options available to product and process designers that allow them to assess the extent to which their design decisions reduce OHS risk in construction, and offering a more rigorous comparison of the OHS risks in IBS and traditional approaches. It is anticipated that the model may provide a way for designers to integrate process knowledge and awareness of safety and OHS risk variables into design to eliminate or reduce hazards in construction. Keywords: IBS, OHS in construction, knowledge-based energy damage model, off-site construction